Pengaruh Transparansi Pajak Oleh Fiskus Dan Trust Terhadap Kepatuhan Wajib Pajak: (Studi Kasus Pada Wajib Pajak Orang Pribadi di Kabupaten Belitung Timur) - Dewi Kusuma Wardani; Adia Adi Prabowo; Arwiyah Nurul Aini (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to examine whether tax transparency by the tax authorities and trust has an effect on taxpayer compliance. This study uses a quantitative description method and primary data using a questionnaire distributed online via google form. The number of samples in this study were 111 individual taxpayer respondents in East Belitung Regency. Sampling in this study used a convenience sampling technique, which is a sampling technique that allows the author to choose a sample based on the author's wishes. This study shows that tax transparency and trust have a positive effect on taxpayer compliance in East Belitung Regency. The results of this study mean that the higher the transparency provided by the tax authorities and the less taxpayers to the tax authorities, the higher the taxpayer compliance will be. Fiskus is expected to be able to further increase the socialization of the new tax provisions and be more open about the amount of tax revenue and its allocation both at the central tax office and at the pratama office.